EFEKTIVITAS PELAKSANAAN TUGAS LURAH DALAM PENYELENGGARAAN PEMERINTAHAN DI KELURAHAN PANIKI BAWAH KECAMATAN MAPANGET KOTA MANADO - BOJOH, SINDY; TULUSAN, FEMMY; DENGO, SALMIN (Sam Ratulangi University, 2019)
The purpose of this study was to determine the supervision of the Sub-District Head in the administration ofvillage governance in the Mandolang District of Minahasa Regency. This study uses a descriptive-qualitativeapproach. The research informants were the Mandolang Sub-District Head, Mandolang District GovernmentSection Head, two Village Heads, two BPD chairmen, and two LPM chairmen; a total of 10 informants. Datacollection uses interview guidelines, while the analytical technique used is the analysis of interactive modelsfrom Miles and Huberman. Based on the results of data analysis, conclusions were drawn: (1) Direct Sub-District Head oversight of village administration is carried out well through observation, observation or directexamination of the village carried out by the Sub-District Head alone or through the assignment ofsubordinates; (2) Sub-district Head indirect supervision is carried out by requesting periodic written reports(every month, quarterly, and every six months) regarding village administration, and village governmentperformance reports at the end of the fiscal year. Indirect supervision also requests oral and explanatoryreports to the village head at the sub-district coordination / evaluation of sub-district. Based on this research itis recommended: (1)The Sub-District Head should go down to villages more often to monitor, observe ordirectly check the running of village administration. (2) The Sub-District Head should check / verify the truthof the written report by visiting the village and having a dialogue with the BPD, LPM, and local villagecommunity leaders.Keywords: Supervision, Sub-District Head, Village Government.